Řízení třídy: studenti učitelství a jejich provázející učitelé - Vlčková, Kateřina (Masaryk University Press, 2020)
Title in English: Classroom Management: Student Teachers and Mentor Teachers. Classroom management is one of the decisive factors in the case of beginning teachers regarding whether they remain in the profession and in the case of experienced teachers regarding their satisfaction in the profession. For beginning teachers, it is an area that they seldom learnt at their faculties and that they learn first in their teaching practice. Yet when teachers are not able to manage their class, they are not able to teach their pupils something either. The monograph presents findings about student teachers in their teaching practice and their mentor teachers at lower secondary schools. Our research is based on classroom observation, interviews, and questionnaires. We study behavioural and instructional management and describe their relation to need for closure.